Using Structural Equation Modeling to Examine Pathways Between Environmental Characteristics and Perceived Restorativeness on Public Rooftop Gardens in China - Chen, Zhanglei; Gan, Kar Kheng; Zhou, Tiejun; Du, Qingfeng; Zeng, Mingying (Frontiers in Public Health, 2022)
As a kind of informal green space more closely related to the built environment, public rooftop gardens (PRGs) are novel green open space and important salutogenic resource for urban residents. It is one of the most easily accessible method for urban residents to be in contact with outdoor or natural elements from the context of high-altitude living. Given its potential health benefits to city dwellers, existing empirical studies are heavily focused on immediate recovery through visually accessing PRGs (through windows), neglecting the possibility of using PRGs physically as a place of interaction. This paper hypothesizes usage patterns will mediate the associations between the environmental characteristics of PRG and users’ restoration. This is done through inputting data from 12 typical samples of PRG in Chengdu, China into structural equation model (SEM). Combining the concept of Perceived Sensory Dimensions (PSD) and Perceived Restorativeness Scales (PRS) with the usage patterns of the above samples, this study aims to examine the correlation of environmental characteristics, usage pattern and restoration, in which identify their relative importance in the context of PRGs. Through serials of numerical tests on the model, the study shows that out of the 20 theoretical pathways constructed by the environmental characteristics (x)–usage patterns (m)–restorative effect (y), only 14 forms a significant correlation. In addition, out of all PSDs, social, serene, refuge, space and nature dimensions are induced into restorative effects through four patterns of use: retreat, nature touch, interpersonal interaction and family-bonding activities. The findings also show that social and family-bonding are the most influential independent and mediating variables respectively in achieving restorative effects in the PRG. This study reveals important findings about how usage patterns mediate the association between the PSD and PRS of users. And it also has generated practical implications on how we can design public rooftop gardens from the perspective of restoration, which could potentially be the key to the future survival and development of PRGs in urban environments.